2020
DOI: 10.3130/aije.85.351
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Dehydration by Water Intake and Ventilated Working Wear at a Construction Site in Summer

Abstract: To obtain basic data for prevention of heat stroke during construction work in a hot environment, we analyzed the effects of wearing ventilated work wear (VWW) and the sweat rate (SR), the rate of water intake (RWI), and body weight loss (RBWL) in experiments of an artificial climate chamber and outside construction site in August. We supposed there is a limit to the amount of water that workers in a construction site can drink. Thus, we verified that RBWL increased with increasing WBGT mainly due to insuffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Since the publication of the Japanese version of this paper, we have been conducting research regarding the effectiveness of VWW. Yamazaki et al analyzed the data obtained in this study in more detail and reported it in a Japanese version of the paper 8 . The analysis demonstrated that there is a limit to the amount of water that workers at a CS can drink, and it was verified that, in the CS setting, the BWL increased with increasing wet bulb globe temperature mainly due to insufficient rate of water intake (RWI).…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Since the publication of the Japanese version of this paper, we have been conducting research regarding the effectiveness of VWW. Yamazaki et al analyzed the data obtained in this study in more detail and reported it in a Japanese version of the paper 8 . The analysis demonstrated that there is a limit to the amount of water that workers at a CS can drink, and it was verified that, in the CS setting, the BWL increased with increasing wet bulb globe temperature mainly due to insufficient rate of water intake (RWI).…”
Section: Introductionmentioning
confidence: 70%
“…Yamazaki et al analyzed the data obtained in this study in more detail and reported it in a Japanese version of the paper. 8 The analysis demonstrated that there is a limit to the amount of water that workers at a CS can drink, and it was verified that, in the CS setting, the BWL increased with increasing wet bulb globe temperature mainly due to insufficient rate of water intake (RWI). The findings suggested that BWL could be partly decreased by using VWW, which decrease the sweat rate.…”
Section: Introductionmentioning
confidence: 90%